Exploring the impacts of purslane extract: a novel supplement for improving physiological and immunological responses in Labeo catla fingerlings - Faisal, Muhammad; Hussain, Syed Makhdoom; Sarker, Pallab K.; Ali, Shafaqat; Al-Ghanim, Khalid A. (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe application of therapeutic plants in aquaculture has gained considerable worldwide attention and is currently the focus of ongoing scientific research. These plants possess diverse bioactive compounds that offer safer, non-toxic, biodegradable, and biocompatible alternatives for consumers. This research assessed the efficacy of purslane extract supplementation on sunflower meal (SFM)-based diets (iso-nitrogenous, iso-lipidic, and iso-caloric) in terms of growth, improving carcass, mineral content, hematology, immune responses, and antioxidant status in Labeo catla fingerlings.MethodsEach of the seven test diets—T0 (no extract supplementation), T1 (0.5% supplementation), T2 (1% supplementation), T3 (1.5% supplementation), T4 (2% supplementation), T5 (2.5% supplementation), and T6 (3% supplementation)—were administered two times per day at a rate equivalent to 5% of their body mass. The experiment was maintained in V-shaped steel tanks for a duration of 90 days. Each group included 15 fingerlings (N = 315; average weight: 7.36 ± 0.03 g), and each diet was administered in triplicates.ResultsBased on the results of the current study, it is clear that the T3 (1.5% supplementation) diet showed significantly improved growth (in terms of percentage weight gain), feed utilization, and whole-body protein content. In addition, the incorporation of 1.5% purslane extract in SFM-based diets significantly enhanced hematological indices, including platelets, red blood cells, hemoglobin, and white blood cells. Furthermore, all the examined diets exhibited a significant (p < 0.05) increase in mineral content. Dietary supplementation with 1.5% purslane extract exhibited significant enhancements in antioxidant defenses, including increased superoxide dismutase, catalase, and glutathione peroxide activities, alongside a marked decrease in malondialdehyde levels. Furthermore, immune parameters, such as lysozyme activity and total globulins levels, showed considerable improvements in response to the 1.5% purslane supplementation.DiscussionThis study suggested that 1.5% purslane extract supplementation is the optimum level for improving the health and physiology of L. catla fingerlings. The therapeutic benefits of purslane may be attributed to its bioactive compounds, which contribute significantly to enhancing fish performance.